2011
DOI: 10.1136/annrheumdis-2011-200182
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of HLA-DRB1*03 and smoking for the development of anti-Jo-1 antibodies in adult idiopathic inflammatory myopathies: a European-wide case study

Abstract: ObjectivesHLA-DRB1*03 is strongly associated with anti-Jo-1-positive idiopathic inflammatory myopathies (IIM) and there is now increasing evidence that Jo-1 antigen is preferentially expressed in lung tissue. This study examined whether smoking was associated with the development of anti-Jo-1 antibodies in HLA-DRB1*03-positive IIM.MethodsIIM cases were selected with concurrent information regarding HLA-DRB1 status, smoking history and anti-Jo-1 antibody status. DNA was genotyped at DRB1 using a commercial sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
81
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(86 citation statements)
references
References 30 publications
3
81
0
2
Order By: Relevance
“…In addition to genetic factors, some environmental factors may also affect MSA expression. Chinoy et al demonstrated an interaction between DRB1*03 and smoking in the development of anti-Jo-1 antibodies [17]. A study in central Japan showed that from 1994 to 2010, the relative prevalence of CADM and anti-MDA-5-antibody-positive patients increased significantly, and the presence of anti-MDA-5 antibodies was inversely associated with the population of the patients' city of residence [18].…”
Section: Discussionmentioning
confidence: 97%
“…In addition to genetic factors, some environmental factors may also affect MSA expression. Chinoy et al demonstrated an interaction between DRB1*03 and smoking in the development of anti-Jo-1 antibodies [17]. A study in central Japan showed that from 1994 to 2010, the relative prevalence of CADM and anti-MDA-5-antibody-positive patients increased significantly, and the presence of anti-MDA-5 antibodies was inversely associated with the population of the patients' city of residence [18].…”
Section: Discussionmentioning
confidence: 97%
“…While the IIM, like other autoimmune diseases, are thought to develop as a consequence of chronic inflammation resulting from environmental exposures in genetically susceptible individuals, few examples of such gene-environment interactions have been reported 30,31 , and none have explained the strong association between AH8.1 and the different myositis phenotypes. The facts that HLA genes: (a) are important in responses to many infectious and noninfectious environmental exposures 32 ; and (b) determine one’s capacity to produce antibodies including many autoantibodies 33 , could explain why specific combinations of HLA alleles are important to the pathogenesis of myositis.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has accumulated that smoking is a triggering factor for the development of anticitrullinated peptide antibodies in RA 13. In IIM, anti-Jo-1 antibody positive cases are more likely to be smokers, which suggests that smoking and the lung play important roles in IIM development as well 14. A recent case–control study showed that a history of lung disease (sarcoidosis, pneumonia or tuberculosis) reported via questionnaire was associated with IIM, providing further evidence that IIM could start in the lung 15…”
Section: Introductionmentioning
confidence: 99%